PENGARUH PENERAPAN PEMBELAJARAN SEJARAH BERBASIS MEDIA BENTENG PORTUGIS (MESS KUPALEH) SEBAGAI REVITALISASI CULTURE HERITAGE DI SMA NEGERI 2 INDRAJAYA - Muslem, Muslem; Fahrizal, Fahrizal; Aisy, Rishazatul (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2023)
This research is entitled Learning History Based on Portuguese Fort Media (Mess Kupaleh) as Revitalization of Cultural Heritage in Indrajaya 2 State Senior High School, the purpose of this study is (1) To find out the application of Portuguese fortress (Mess Kupaleh) media-based learning as Revitalization of Cultural Relics in Public Senior High Schools 2 Indrajaya. (2) To find out the supporting and inhibiting factors of Learning History Based on Portuguese Fort Media (Mess Kupaleh) as Revitalization of Cultural Heritage in Indrajaya 2 Public High School. The approach used in this study is a quantitative approach. This research is included in the type of experimental research. The data collection technique used is the observation method, the interview method and the documentation method. Meanwhile, the data analysis technique is the quantitative data analysis technique. The results of the research Based on the results of data processing, the value of tcount = 4.26 while ttable = 1.68, so that the Fortress Media-Based History Learning Course can improve student achievement and interest in learning. Supporting Learning Factors History Based on Portuguese Fort Media (Mess Kupaleh) As Revitalization of Cultural Heritage in Indrajaya 2 Public High School, namely the existence of sufficient facilities and infrastructure at school, good interaction between teachers and students, availability of sufficient history learning time, and factors from individual students themselves, as well as environmental factors that are also very decisive. Inhibiting factors for Learning History Based on Portuguese Fort Media (Mess Kupaleh) as Revitalization of Cultural Heritage at Indrajaya 2 State Senior High School include a lack of historical teaching materials, external factors that greatly influence are the school environment, and internal factors the physiological conditions and psychological conditions of students during the learning process. Keywords: Learning History, Portuguese Castle Media (Mess Kupaleh) Revitalization of Cultural Heritage